Evaluasi Kinerja Keuangan PT Bank Syariah Indonesia dengan Pendekatan Risk Profile, Good Corporate Governance, Earnings, dan Capital - Fadhil, Muhammad Irsyad; Nurlaila, Nurlaila; Rahmani, Nur Ahmadi Bi (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2025)
The banking sector has a strategic and essential role to support the economic development of a country. Therefore, banks must be able to manage their operations efficiently in order to maintain customer trust. As a reference for basic tools for authorities to formulate effective supervisory strategies using the provisions of POJK No.4/POJK.03/2016 to assess bank health assessments. This study examines PT Bank Syariah Indonesia (BSI), recognized as the leading Islamic bank in Indonesia, to assess its financial condition using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital) over the 2021-2023 period. The research adopts a quantitative approach and uses descriptive secondary data analysis. The results indicate that BSI is in an